Glucose Detection Based on Light Reflection in Modulated Optical Fibers for Continuous Diabetes Monitoring - Mahmudah Salwa Gianti; Ahmad Fauzi; Muhammad Rizalul Wahid; Taufik Ridwan; Tri Seda Mulya (Journal of Electrical, Electronic, Information, and Communication Technology, 2024)
Diabetes mellitus is a chronic disease characterized by elevated blood glucose levels. Approximately 463 million adults worldwide have diabetes, and nearly half of them remain undiagnosed. Early diagnosis and treatment of diabetes are crucial to prevent serious complications. Continuous glucose monitoring (CGM) offers numerous advantages over traditional fingertip blood glucose measurements. CGM allows patients to track their glucose levels in real time, identify patterns, and adjust their diet and medication appropriately. This research presents a novel optical fiber-based glucose sensor utilizing the macrobending modulation technique. This method offers several advantages, including ease of use, low cost, and strong signal generation. The sensor exploits the refractive index difference between the glucose solution and the optical fiber. Variations in glucose concentration induce changes in the refractive index, which are converted into voltage signals. The sensor exhibits a sensitivity of 337 mV/decade and demonstrates a linear relationship between the voltage signal and glucose concentration within the range of 0-10 mM. The macro bending-modulated optical fiber sensor shows potential as a simple, cost-effective, and efficient CGM tool. Further research is necessary to enhance the sensor's sensitivity and stability and to evaluate its performance in biological samples.